TA'ZĪR METHOD AS AN INSTRUMENT FOR CHARACTER DEVELOPMENT OF STUDENTS IN ISLAMIC BOARDING SCHOOL - Mohamad Alfan Niam; Ahmad Saefudin (Fakultas Tarbiyah, Universitas Ibrahimy, 2026)
This study investigates the application of the ta’zīr method to cultivate disciplinary character among students at Pondok Pesantren Daruttauhid Al Alawiyyah Jepara. The research arises from the essential role of discipline in shaping responsible and virtuous individuals, as well as from the need to reinterpret ta’zīr as a pedagogical practice rather than merely a punitive act. Employing a qualitative case study design, data were collected through in-depth interviews, participatory observation, and document analysis with caregivers, administrators, and students as key informants. Data analysis followed the Miles and Huberman interactive model, encompassing data reduction, data presentation, and conclusion drawing. The findings indicate that ta’zīr is implemented in a wise, proportional, and educational manner, tailored to the level of violation and individual circumstances of the students. This approach has proven effective in fostering discipline, responsibility, moral awareness, and social cohesion within the pesantren community. Supporting elements such as exemplary leadership, a religiously nurturing environment, and open communication further enhance the success of ta’zīr. Overall, the research offers valuable insights into developing character-building strategies in Islamic educational settings by balancing firmness and compassion.